2016
DOI: 10.1108/vjikms-08-2014-0052
|View full text |Cite
|
Sign up to set email alerts
|

Organizational performance through the donation and collection of interorganizational knowledge

Abstract: Purpose – This paper aims to provide empirical evidence to support the relationship between interorganizational knowledge sharing, absorptive capacity and organizational performance, and proposes that interorganizational knowledge sharing is composed of two processes: knowledge donation and collection. Design/methodology/approach – A quantitative methodology is adopted to examine the proposed relationship between interorganizational know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
(92 reference statements)
5
25
1
2
Order By: Relevance
“…The results of the study contradict the findings of Nodari et al (2016), that the capability of knowledge absorption has a significant effect on Performance. Knowledge sharing has a significant effect on employee performance.…”
Section: Figure 2 the Results Of Structural Equation Modelcontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the study contradict the findings of Nodari et al (2016), that the capability of knowledge absorption has a significant effect on Performance. Knowledge sharing has a significant effect on employee performance.…”
Section: Figure 2 the Results Of Structural Equation Modelcontrasting
confidence: 99%
“…The results show that the higher the rate of the decreased absorption capacity of knowledge will increase the performance degradation. Nodari et al (2016) also found that high knowledge absorption capacity will improve performance. H4: Knowledge absorption significantly affects the performance.…”
Section: Knowledge Absorption and Performancementioning
confidence: 95%
See 1 more Smart Citation
“…Finally, with extensive experience in the community, the individual begins to donate knowledge at a greater rate than he/she collects knowledge, as represented by the Donator cluster. This is in line with Hooff and Ridder (), Hooff and Van Weenen (), and Nodari, Oliveira, and Maçada (), who find that the more a person collects, the more he/she donates.…”
Section: Cluster Analysissupporting
confidence: 89%
“…Knowledge sharing can occur between organisations (inter-organisational) or within organisations (intra-organisational) (e.g. Nodari, Oliveira, & Gastaud, 2016;Van Wijk, Jansen, & Lyles, 2008). Although, many studies focus on knowledge sharing within an organisation, organisations could also improve their innovative capabilities by sharing knowledge across organisations (Easterby-Smith, Lyles, & Tsang, 2008).…”
Section: Face-to-face Interactions and Knowledge Sharingmentioning
confidence: 99%